Characteristics and Potential of Nitrogen-fixing Microbes in the Rhizosphere of Corn and Legume Plants on Kisar Island - Mahulette, Ferymon; Pattipeilohy, Mery; Pelamonia, Alamanda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Kisar Island community usually plants legumes and corn in one hole called the hapa planting system. This planting system allows interaction between microbes, especially in the rhizosphere that supports plant growth. This study aims to characterize and test the potential of nitrogen-fixing microbes in the rhizosphere of legumes and corn plants using the hapa planting system. Isolation and characterization of nitrogen-fixing microbes using Yeast extract mannitol agar (YEMA) media added with Congo red and bromothymol blue as indicators. The potential of the microbes tested was the ability to dissolve phosphate using Picovskaya media and cellulolytic using Carboxy methyl cellulose (CMC) media. A total of five isolates of nitrogen-fixing microbes were found each in the rhizosphere of corn and mung beans (JKH) and corn and red beans (JKM) with varying numbers and characteristics. The number of microbes in the JKH rhizosphere was 9.5x102 cfu/g lower than the number of microbes in JKM which was 1.5x103 cfu/g. The highest phosphate-dissolving ability was found in isolate KM5 with a phosphate solubility index of 3.14, while the cellulolytic ability was found in isolate KH1 with a cellulolytic index of 0.80. These potential microbes can be developed as starters for developing biofertilizers on less fertile agricultural land in the future.